Relationship between HIV stage and psychomotor speed neurocognitive score at a Kenyan sub-county hospital - Rachael N. Kinuthia; Joseph M. Thigiti; Benson N. Gakinya (AOSIS, 2016)
Background: Human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) is associated with cognitive impairment which affects psychomotor speed. Psychomotor slowing is a predictor of dementia and death in people living with HIV and AIDS. The purpose of this study was to assess the relationship between HIV disease stage and psychomotor speed neurocognitive score which will add to the body of knowledge required to manage patients with HIV and AIDS. Objective: To determine the relationship between psychomotor speed neurocognitive score and the HIV disease stage in adults at initiation of care. Setting: This study was conducted at Kangundo Sub-county hospital comprehensive care centre. Methods: This was a cross-sectional study. All HIV seropositive patients aged 18 to 50 years recently initiated into care were studied. A pretested questionnaire was used to collect data. The World Health Organization (WHO) stage was used during data collection to classify study participants into asymptomatic and symptomatic groups. The grooved pegboard test was used to obtain psychomotor speed neurocognitive scores. Descriptive statistics were used to summarise data. Mann-Whitney U test, Spearman's rho and multiple linear regression were employed in the analysis; p-value of 0.05 was considered significant. Results: The WHO stage did not have a significant effect on the psychomotor speed neurocognitive score (p ≥ 0.05). The CD4 count had a significant effect on psychomotor speed neurocognitive score (p = 0.001). Conclusions: There was a significant correlation between CD4 counts and psychomotor speed neurocognitive score. Efforts should be made to ensure that the CD4 counts of people living with HIV and AIDS do not continue to fall after initiation into care in order to preserve psychomotor function.